Amphiphilic fluorescent nanospheres for quantitative sensing of trinitrophenol in water system. (June 2022) - Zan, Yuxuan; Kang, Yazhuo; Wang, Bowei; Cui, Siqian; Shen, Zhuoyao; Shu, Jiahui; Kong, Xiangjin; Chen, Ligong; Yan, Xilong; Li, Yang
Abstract: 2, 4, 6-Trinitrophenol (TNP) is an important chemical and widely applied in industry. However, on account of its high toxicity, flammability and explosive nature, just trace amounts of TNP may cause potential threats to ecosystem and human security, so it is significant to establish a rapid and reliable method for the detection of TNP. Herein, a novel amphiphilic fluorescent probe TPE-CD was successfully designed and synthesized by the functionalization of hydrophilic β -cyclodextrin with a hydrophobic Aggregation Induced Emission (AIE) fluorophore. Moreover, spherical nanoparticles formed in H2 O/CH3 OH solution with the increase of water fraction ( f w ). Fluorescence titration of TNP indicated that TPE-CD exhibited excellent sensitivity to TNP with LOD = 0.31 μmol L −1 and Ksv  = 3.06 × 10 4  L mol −1 . The introduced β -cyclodextrin remarkably enhanced the ability of TPE-CD rather than its precursor TPE-COOH to capture TNP molecules through forming spherical nanoparticles, improving the fluorescence quenching efficiency. Density Functional Theory (DFT) calculations and experimental results confirmed that the response mechanism of TPE-CD to TNP involved Photoinduced Electron Transfer (PET) and Fluorescence Resonance Energy Transfer (FRET) with PET being predominant. Furthermore, the probe showed excellent selectivity and anti-interference to aqueous TNP samples. Moreover, the test strips prepared by soaking in TPE-CD solution also exhibited good sensitivity to TNP, providing a convenient, rapid and reliable method for the detection of TNP. Graphical abstract: Image 1 Highlights: An amphiphilic fluorescent probe TPE-CD for TNP was constructed by the functionalization of β -cyclodextrin with AIE group. High sensitivity and selectivity to TNP with LOD of 0.31 μmol L −1 in water was achieved. The response mechanism was the integrated results of PET and FRET with PET being predominant. Test strips prepared by TPE-CD solution exhibited nice sensitivity to TNP. This work provided a convenient, rapid and reliable method for TNP detection.